2007
DOI: 10.1007/s10551-007-9399-z
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Familism in the Global Era: A Study on the Recent Development of the Ethnic-Chinese Business, with Particular Attention to the Indonesian Context

Abstract: Chinese culture, Chinese-Indonesian, christian theology of family, Confucianism, corporate values, family business, globalisation, inter-generational succession, racial discrimination,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 6 publications
0
14
0
4
Order By: Relevance
“…Thus, familism is associated with loyalty and commitment towards own group (Ho & Barnes, 2013). Moreover, familism makes work relations personal and flexibile to change (Wijaya, 2008). Her study revealed that the Malaysian entrepreneurs prioritise advice and support from their family members, sharing knowledge and resources and seek help from their loyal and trusted employees.…”
Section: H6: Impact Of Familism On Business Growthmentioning
confidence: 99%
“…Thus, familism is associated with loyalty and commitment towards own group (Ho & Barnes, 2013). Moreover, familism makes work relations personal and flexibile to change (Wijaya, 2008). Her study revealed that the Malaysian entrepreneurs prioritise advice and support from their family members, sharing knowledge and resources and seek help from their loyal and trusted employees.…”
Section: H6: Impact Of Familism On Business Growthmentioning
confidence: 99%
“…Her study indicated that the Malaysian entrepreneurs give more importance in receiving support and advice from members of their family, sharing resources and knowledge with close associates to overcome obstacles in managing their businesses and also identify and seek help from their trusted employees. Thus, familism assists the firm to develop a community of trust within business network as well as within its internal structure (Wijaya, 2008).…”
Section: Familismmentioning
confidence: 99%
“…Her findings also showed that the Malaysian entrepreneurs stretch more importance in getting support besides advice from their family members, sharing resources and knowledge with close associates to overcome obstacles in managing their businesses and also identifying and seeking help from their trusted employees (Barney, 1991;Buckley et al, 1988). Thus, familism assists the firms to develop a community of trust within the business network as well as within its internal structure (Wijaya, 2008).…”
Section: Literature Reviewmentioning
confidence: 94%